Severe corneal burn due to accidental application of salicylic acid packed in a plastic dropper bottle (2020)
Eye burns by accidental application of substances, pharmacological or non-pharmacological, packaged in plastic dropper bottles, have been described for more than three decades, and continue to occur. These burns can cause potentially serious corneal injuries. We present the case of a patient who mistakenly applied salicylic acid to the right eye, when confusing it with an eye lubricant, causing a severe corneal burn. Fortunately, after aggressive medical and surgical management (including oxygen therapy and amniotic membrane grafting) the visual results were good. We suggest conducting educational campaigns and also taking legislative measures in our country to avoid the packaging of corrosive substances in this type of dropper bottles, in order to reduce the risk of accidental burns. © 2020, Instituto Nacional de Salud.